Real-time calculation of the initial angle of projection for fragments in cylindrical warheads. (October 2022) - Felix, David; Colwill, Ian; Harris, Paul
This paper presents an improvement in the speed and accuracy of calculating the initial angle of projection of fragments for exploding cylindrical shells. It is a fast tool that can be used by designers, where existing approaches, such as computationally intensive Finite Element Analysis, are preventively slow. An enhanced Taylor equation is presented using available experimental data and the effect of the changing shape of the warhead's cylindrical casing on the fragment's initial projection angle. The resulting equation is computationally fast as it uses uncomplicated equations and provides improved accuracy for estimating a fragment's initial angle of projection in comparison to existing work.